'Selfish herders' finish last in mobile animal groups. Issue 1985 (26th October 2022) - Sankey, Daniel W. E.
Abstract : Predation is a powerful selective pressure and probably a driver of why many animal species live in groups. One key explanation for the evolution of sociality is the 'selfish herd' model, which describes how individuals who stay close to others effectively put neighbours between themselves and a predator to survive incoming attacks. This model is often illustrated with reference to herds of ungulates, schools of fish or flocks of birds. Yet in nature, when a predator strikes, herds are often found fleeing cohesively in the same direction, not jostling for position in the centre of the group. This paper highlights a critical assumption of the original model, namely that prey do not move in response to position of their predator. In this model, I relax this assumption and find that individuals who adopt 'selfish herd' behaviour are often more likely to be captured, because they end up at the back of a fleeing herd. By contrast, individuals that adopt a rule of 'neighbour to neighbour alignment' are able to avoid rearmost positions in a moving herd. Alignment is more successful than selfish herding across much of the parameter space, which may explain why highly aligned fleeing behaviour is commonly observed in nature.